Significant effect on annealing temperature and enhancement on structural, optical and electrical properties of zinc oxide nanowires - Paiman, S.; T., Hui Ling; Husham, M.; Sagadevan, Suresh (Elsevier BV, 2020)
This paper focused on the growth of zinc oxide nanowires on unannealed and annealed indium tin oxide-coated-coated glass substrates on the structural, optical, and electrical properties towards surface acoustic wave (SAW) piezoelectric nanodevices. Zinc oxide nanowires (ZnO NWs) were grown onto Indium Tin Oxide (ITO)-coated glass substrates by a chemical bath deposition method. The growth of ZnO NWs carried onto unannealed and annealed Indium Tin Oxide-coated glass substrates. Substrates were annealed at 400 °C for 90 min at ambient using a horizontal furnace. This work also focused on the effect of annealing condition of ITO-coated glass substrate on nanowires morphology, crystal phase, optical band gap, and electrical properties. Substrate annealing was found to have a significant effect on the nanowires dimension. The nanowire's morphology was obtained by FESEM which the average diameter and length found on unannealed ITO-coated glass substrate were 674.18 ± 26.75 nm and 3.107 ± 0.446 μm. However, the nanowire's average diameter and length on annealed ITO-coated glass substrate were 393.50 ± 27.02 nm and 3.175 ± 0.321 μm. XRD analysis confirmed that ZnO nanowires on substrates with both conditions were able to promote the growth of crystal structure with crystal plane orientation of (1 0 1) and (1 0 0) belongs to hexagonal wurtzite structure. The near-band-edge (NBE) emission of ZnO nanowires obtained by using Photoluminescence which grown on unannealed and annealed ITO-coated glass substrates were observed at 380 nm (3.20 eV) and 384 nm (3.23 eV). FTIR analysis showed that ZnO absorption bands in the region between 450 and 500 cm−1 had arisen from interatomic vibrations due to the stretching of the Znsingle bondO bond. The resistivity of ZnO nanowires obtained by using the four-point probe method on unannealed and annealed substrates was found to be 2.0675 × 10−7 Ω cm and 2.0494 × 10−7 Ω cm.